Frequency of erotic dreams and relationship status: an online study - Schredl, Michael; Göritz, Anja (International journal of dream research, 2020)
So far, the association between relationship status and the frequency of erotic dreaming has rarely been studied. Within this survey, 823 participants (467 females, 356 males; mean age: 49.24 ± 13.45 years) completed a retrospective question about the percentage of erotic dreams in relation to all remembered dreams. The findings indicated that relationship status (single vs. having a stable partnership) was not related to the percentage of erotic dreams. Solely, widowed persons dreamed relatively seldom about erotic topics. Future studies eliciting erotic activities during the day, including indulging in erotic fantasies, could help to clarify whether the findings of the present study can be explained by the hypothesis that erotic dreams more likely reflect erotic fantasizing during the day than actual sexual activities.
Gesehen am 07.04.2020